Evaluasi Kinerja Pengelolaan Pabrik Karet Remah: Studi Kasus di Sumatera Selatan - Suwardin, Didin (Jurnal Agro Industri Perkebunan, 2015)
Indonesia as the world's second largest natural rubber producer, products derived predominantly (> 90%) in the form of crumb rubber. In the management of crumb rubber factoryshould basically be dynamic is to follow developments in technology and customer requirements, as well as efforts to increase competitiveness. To determine the performance of crumb rubber factory on the current and future compliance requirements have made observations on the management of crumb rubber factory. This research was conducted using a survey of crumb rubber factory in South Sumatera province. Determination respondents crumb rubber factory done intentionally (purposive sampling) the criteria for the location of the plant, production capacity, production processes, energy use, and production control. Survey activities conducted in crumb rubber factory located in Musi Banyuasin, Muara Enim and Banyuasin districts, as well as four factories located in the city of Palembang. Parameter observations include raw rubber material conditions, contamination control, energy aspects of processing, and the malodor control. The survey results indicate the selectivity in the purchase raw rubber material by the crumb rubber factories decreased due to competition tightly, it could have an impact on the risk of contamination problems in products SIR. Management of crumb rubber factories have sought to convert the use of fossil fuel resources  to materials that are environmentally friendly. Tata factory work generally show has been categorized as good, there is even a plant considered to be very good, fairly intensive use of labor inspectors in some parts of the process and the results are assessed effectively. Odor problems at the crumb rubber factories can be reduced by using good air circulation room and poring Deorub into blanket  before the drying.Keywords: consistency, contaminant, crumb rubber, energy, factory, quality, raw materialPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/24